Rancang Bangun Website Posyandu Kasih Ibu Kelurahan Kelapa Indah Tangerang - Martono Martono; Dedeh Supriyanti; Irvan Firmansyah (UNIVERSITAS RAHARJA, 2020)
Posyandu is one of the community-based basic health activities organized from, by and for the community assisted by health workers. Posyandu activities also require an Information System to improve the performance of health services for the community, especially in the data management process. Posyandu Kasih Ibu Kelurahan Kelapa Indah Tangerang is currently still using paper and handwritten media in all Posyandu activities, including registration, data collection for pregnant women and children under five. This of course has many shortcomings that can hinder the process of Posyandu activities. Referring to the results of the analysis that has been carried out directly, the existing system requires changes, therefore the main objective of this study is to create a Posyandu system that is able to process data management to be displayed in the form of information and reports quickly, accurately and useful. . The system to be designed is Web-based with the Hypertext Prepocessor (PHP) programming language and MySQL database, so the results of this study are a website for the Kasih Ibu Posyandu, Kelapa Indah Village, Tangerang.